Validation of 3D skin imaging for objective repeatable quantification of severity of atrophic acne scarring. Issue 4 (6th March 2018) - Petit, L.; Zugaj, D.; Bettoli, V.; Dreno, B.; Kang, S.; Tan, J.; Torres, V.; Layton, A. M.; Martel, P.
Abstract: Background: One major sequelae of acne is atrophic scarring, yet objective tools to assess scars are lacking. Neither depth nor volume of atrophic scars is readily evaluable clinically and standard 2D photography is significantly affected by lighting and shadows. The aim of our study was to define and evaluate parameters of 3D imaging that can be used to assess severity of atrophic acne scarring. Methods: Single center study of 31 patients with acne scarring. A target area of 3 × 3 cm was defined on the face. The global severity of atrophic acne scarring in the target area was evaluated by 5 dermatologists and scars were counted and categorized by size (scars < 2 mm, 2‐4 mm, and > 4 mm in diameter). Three dimensional images of the target area were acquired with the LifeViz Micro ® system and analysis was performed using MountainsMaps ® software. An algorithm was developed to quantify the scar volume loss: shape removal step, with an order 5 polynomial, and to calculate the Valley void volume 80% (Vvv 80%) defined in the ISO‐25178 standard for 3D surface texture. Results: Correlation coefficient of the Vvv parameter to mean global severity at the target area rating was 0.77. The volume of scars evaluated with the Vvv parameter was mainly impacted by scars > 2 mm. The evaluations demonstrated good repeatability (with an intra‐class correlation coefficient ICC = 0.98). Conclusions: We demonstrate convergent validation to clinical assessment and repeatability of 3D skin imaging in atrophic acne scarring. Image analysis is straightforward and can be integrated into an automated workflow.